Development and applications of three-dimensional gamma ray tomography system using ray casting volume rendering techniques - Oliveira Jr., J. M. de; Lima, F. Z. C. de; Milito, J. A. de; Martins, A. C. G. [UNESP] (Sociedade Brasileira de Física, 2005)
Computed Tomography (CT) has made possible visualization of physical structures in the interior of an object in their real relative spatial position and orientation. Another important contribution of CT is to greatly improve abilities to distinguish regions with different gamma ray transmittance and to separate over-lying structures. The mathematical problem of CT imaging is that of estimating an image from its projections. In this work, the experimental setup was performed using the Mini Computerized Tomograph of Uniso (MTCU). This tomograph system operates with a gamma ray source of 241Am (photons of 60 KeV and 100 mCi of intensity) and a NaI(Tl) solid state detector. The system features translation and rotation scanning modes, a 100 mm effective field of view, 1 mm of spatial resolution and 5 % to 10 % of density resolution. The image reconstruction problem can be solved using two different algorithms: Algebraic Reconstruction Techniques (ART) or Discrete Filtered Backprojection (FBP). The three-dimensional image reconstruction method discussed in this work, involves obtaining two-dimensional (2D) gamma ray tomography images and then combining these images into a three-dimensional (3D) volume data. An opacity, shading and color is attributed to each volume element (voxel) and the resulting scene is projected in a picture plane to be display in a monitor. Our implementation was developed to be used with MTCU data and was based in the Ray casting volume rendering technique. The use of such technique for nondestructive evaluation is a powerful tool to enable a visual trip inside an object without physically opening or cutting it. Experimental and theoretical methods used are discussed and results of experiments using the 3D reconstruction techniques are presented. A particular use of this technique to study concrete properties, such as stones distributions, visualization of structural occurrences inside concrete samples is discussed.